Intellectual property damages : - Glick, Mark A. (J. Wiley, 2003)
A comprehensive resource for anyone involved in intellectual property litigation. As the number of cases involving intellectual property (IP) increases, so does the demand for individuals who can create, support, and prove an effective theory of damages in those cases. Intellectual Property Damages presents the basics of intellectual property, the litigation process, the essential "rules" in postulating damages theories, the economic principles that are the foundation for much of IP damages, and the skills necessary to correctly calculate damages in IP cases. Legal professionals and their clients will benefit from the unique combination of knowledge acquired from the author’s experience with law, economics, accounting, and (to a more limited extent) finance in the context of IP damages theories. Intellectual Property Damages contains case summaries, useful forms for discovery, examples of effective expert opinions and testimony, and detailed calculations under various theories of damages. It also incorporates graphs illustrating economic principles, equations that might be used to support (or detract from) a damages theory, and examples of legal documents that commonly appear in IP litigation.